A grey-box model identification of an advanced oxidation process for wastewater treatment. Issue 28 (2015) - Abouzlam, Manhal; Ouvrard, Régis; Poinot, Thierry; Mehdi, Driss; Pontlevoy, Florence; Gombert, Bertrand; Vel Leitner, Nathalie Karpel
Abstract: This paper deals with a grey-box model identification of a catalytic ozonation pilot process used in wastewater treatment. The grey-box model is presented. For the parametric estimation, a non convex optimization problem must be solved. Then, we propose to solve this problem, in practice, by using a Levenberg-Marquardt algorithm applied to a composite criterion based on a priori knowledge which imposes a physical meaning to the solution. The method is applied to experimental data.